MANAGEMENT TOUR GUIDELINES TO TOURISM SATISFACTION IN NORTH SUMATERA - INDONESIA - Sri Rahayu, Yanti Hasbian Setiawati, Tumiran, Muhammad Isa Indrawan, Siti Aminah, (International Journal of Advanced Science and Technology, 2020)
This research is the Effect Of Tour Guide Knowledge and Skills on Tourist Satisfaction Mediated by Trust in Lake Toba, North Sumatra. The focus of this research is the satisfaction of tourists can be created through quality and service, with good skills by a tour guide, tourists will get new knowledge and experience of attractions described by the tour guide. If both the services provided, the image of tourism and tour guides will be able to meet the needs and desires of tourists. The purpose of this study was to determine whether there is a significant influence of tourist knowledge and tour guide skills on tourist satisfaction both partially and simultaneously. This type of research in this study is associative research that measures the association between two or more variables. Samples taken using a questionnaire amounted to 61 tourists. The data analysis technique used in this study is multiple linear regression analysis. The results showed that knowledge partially had a significant effect on Tourist Satisfaction, partially the skills and trust of the tour guide did not significantly influence Tourist Satisfaction and simultaneously knowledge of the Tour Guide had a significant effect on Tourist Satisfaction. Therefore, given that tour guide knowledge and skills have a significant influence on tourist satisfaction at lake toba in north Sumatra, it is expected that tour guides must pay attention to the factors of tour guide knowledge about tourism objects and tour guide skills.